A Hybrid Strategy for Patients With Complex Cerebral Aneurysm: STA–MCA Bypass in Combination With Endovascular Embolization - Wang, Gang; Zhang, Xi'an; Gou, Yanxia; Wen, Yunyu; Zhang, Guozhong; Li, Mingzhou; Zhang, Shichao; Yin, Yanyi; Chen, Siyuan; Qi, Songtao; Feng, Wenfeng (Frontiers in Neurology, 2021)
Objective: To present our experience of patients with complex cerebral aneurysm treated with a hybrid approach: superficial temporal artery-middle cerebral artery (STA-MCA) bypass in combination with endovascular exclusion of the aneurysm. Method: Patients with aneurysms deemed unclippable and uncoilable were included. All patients were treated with a hybrid approach. After STA-MCA bypass, the parent artery was temporarily occluded. If the intraoperative motor evoked potential (MEP) and somatosensory evoked potential (SEP) waveforms remain normal and last for 30 minutes, the aneurysm and parent artery will be embolized permanently with detachable balloons or coils. Results: 20 patients with 22 aneurysms were included in this study. There were 13 women and 7 men with an average age of 42.5 years. Intraoperative angiography showed good patency of all the STA grafts, and neither SEP nor MEP abnormalities was detected. After the parent artery and aneurysm was occluded, the intraoperative angiography showed immediately successful exclusion of the aneurysm in 20 aneurysms, and immediate contrast stasis in 2. All patients recovered uneventfully without ischemic or hemorrhagic complication. Angiography at 6-month follow-up showed total obliteration in 20 aneurysms. 2 aneurysms showed residual and were recoiled. All STA grafts showed good patency and the mean graft flow was 124.2 ml/min. Conclusion: STA-MCA bypass in combination with endovascular exclusion is an appropriate option for patients with complex cerebral aneurysms that are not amenable to direct surgical clipping or endovascular embolization.